Effects of ethinyl estradiol-containing oral contraception and other factors on body composition and muscle strength among young healthy females in Finland—A cross-sectional study. (January 2019) - Suuronen, Juha; Sjöblom, Samu; Tuppurainen, Marjo; Honkanen, Risto; Rikkonen, Toni; Kröger, Heikki; Sirola, Joonas
Abstract: Objective: The aim of this cross-sectional study was to determine the association of hormonal contraception and other life-style factors and habits affecting body composition (BC) and muscle strength. Study design: We measured the body composition of 400 healthy Finnish women (aged 20–40 years) using total body dual energy x-ray absorptiometry (TB-DXA) as well as grip strength (GS [kPa]) with a hand-held dynamometer and knee extension strength (KES [kg]) between 2011 and 2014. Investigated body composition variables were appendicular skeletal mass (ASM [kg]), body mass index (BMI [kg/m 2 ]), relative skeletal muscle index (RSMI [ASM/m 2 ]), total lean mass (TLM [kg]), skeletal muscle index (SMI [TLM/weight × 100]) and fat-%. Participants filled out a questionnaire concerning life-style factors and habits: hormonal contraception, physical activity, alcohol consumption, age, pregnancies, smoking and self-assessed health that were also adjusting factors in the covariate model. We investigated the effects of hormonal contraception and other life-style factors and habits on body composition and muscle strength using AN(C)OVA in the analyses. Results: Women using hormonal contraception with the combination of ethinyl estradiol + progestogen had significantly lower mean ASM (18.0), RSMI (6.5), TLM (40.8) (p < 0.01) and GS (34.6) (p < 0.001) compared to the women not using hormonal contraception with mean values of ASM (18.8), RSMI (6.7), TLM (42.6) and GS (36.9). After adjustment ASM (18.3), SMI (64.3), GS (35.2) (p < 0.05), RSMI (6.6) and TLM (41.2) (p < 0.01) were significantly lower and fat-% (31.4) higher (p < 0.05) compared to women not using hormonal contraception with mean values of ASM (19.0), SMI (66.1), GS (36.7), RSMI (6.8), TLM (42.7) and fat-% (29.8). Conclusion: Use of ethinyl estradiol + progestogen-containing hormonal contraception may have negative association with muscle mass and strength.